Efficient Overlay Multicast Routing for Hybrid Networks - Ali Khan, Imran; Ahmad Madani, Sajjad; Saddique, Mubbashar; Malik, Sana (Malaysian Journal of Computer Science, 2011)
Multicast can be done on link layer, IP layer, and application layer respectively. The application level overlay multicast is easier to deploy as compared to non overlay multicast but at the cost of efficiency. However, the utilization of these approaches is limited by current Internet architecture. Overlay and non overlay integrated solution have not yet been proposed for hybrid networks. In this paper, we propose a novel protocol named Efficient Overlay Multicast Routing (EOMR), in which multilayer multicast methods are integrated and the conversion among these methods is performed dynamically. Moreover, a Multicast Address and Port Translation (MAPT) protocol is used to achieve low-level overlay forwarding in intermediate systems, while the application-level multicast can only be implemented in end systems. The EOMR described here is mainly oriented to the hybrid network, a superset of pure MANET. The performance of EOMR with MAPT is evaluated by comparing it with other multicast protocols proposed for mobile ad hoc networks.